Bridging Generations: Lived Experiences of Seasoned Faculty Members in Adapting to Gen Z’s Learning Behaviors - Karen A Manaig; John Frederick B Tesoro; Melvin T Guache; Chester Alexis C Buama (Journal of Elementary and Secondary School, 2026)
This transcendental phenomenological study explored the lived experiences of seasoned faculty members in adapting to the learning behaviors of Generation Z (Gen Z) students. Ten higher education instructors from one state university, each with at least ten years of continuous teaching experience, were purposively selected as participants. Data were gathered through semi-structured interviews designed to elicit in-depth reflections on their teaching encounters, challenges, and adaptive strategies in addressing the unique characteristics of Gen Z learners. Analysis of the interview data revealed three overarching themes: (a) the evolving learning characteristics and challenges of Gen Z students, (b) adaptive and engaging teaching practices for Gen Z learners, and (c) the effectiveness and responsiveness of adaptive teaching strategies. From these themes, the SAIL Metaphorical Framework was developed to conceptualize effective teaching for Gen Z learners, encompassing four key components: S – Student Characteristics, A – Adaptive Teaching, I – Instructional Effectiveness, and L – Learning Journey. The findings highlight those Gen Z learners’ short attention spans, digital dependence, and varied social behaviors necessitate adaptive, technology-integrated, and student-centered instructional approaches. Seasoned faculty members play a crucial role in bridging generational learning gaps through continuous reflection, innovation, and responsiveness to learner diversity. Ultimately, adaptive teaching emerges as both a pedagogical approach and a transformative process of professional growth, enabling educators to create meaningful and lasting learning experiences that align with the evolving needs of Generation Z students.